Optimizing Mitral Valve Replacement Outcomes: The Role of Goal-Directed Hemodynamic and Fluid Therapy in the Perioperative Period - Ravshan A. Ibadov; Sherzod M. Aliev; Sardor Kh. Ibragimov; Suhrob P. Ergashev (Инновационная медицина Кубани)
Background: There is no doubt that hemodynamic monitoring plays a crucial role in cardiac surgery. Research is generally aimed to identify optimal strategies for maintaining hemodynamic stability, reducing complications, and minimizing recovery time after surgery.Objective: To study the effect of echocardiography-guided goal-directed hemodynamic and fluid therapy on perioperative outcomes of mitral valve replacement (MVR).Material and methods: We analyzed data from 146 patients with mitral regurgitation who underwent MVR. The patients were grouped by standard hemodynamic therapy (comparison group, n=74) and goal-directed therapy (main group, n=72). The study groups were representative, and preoperative clinical, laboratory, and imaging data did not differ significantly between the groups. The study period began with the induction of general anesthesia and ended with hemodynamic stabilization achieved. This point of clinical recovery was defined as the successful extubation and absence of vasoactive support; the dose of inotropes and/or vasopressors was either completely weaned off or remained unchanged for >8 hours.Results: The study groups differed in several key parameters. The anesthesia time decreased from 255 to 223 minutes (P=.02), and the cardiopulmonary bypass time from 94 to 82 minutes (P<.001). The volume of fluids until hemodynamic stabilization was achieved was higher in the comparison group (P=.002). Inotropes were used more often in the comparison group (P><.05). The mechanical ventilation time in the main group and the comparison group was 7.33 and 13 hours, respectively (P><.001); the intensive care unit length of stay was 1.1 and 1.8 hours (P=.014), respectively. The incidence of acute myocardial ischemia was lower in the main group (2.8% vs 12.2%, P=.026). Conclusions: Goal-directed hemodynamic and fluid therapy significantly improves MVR outcomes and reduces the risk of postoperative complications and long-term use of cardiovascular drugs.> <.001) . The volume of fluids until hemodynamic stabilization was achieved was higher in the comparison group (P=.002). Inotropes were used more often in the comparison group (P <.05) ). The mechanical ventilation time in the main group and the comparison group was 7.33 and 13 hours, respectively (P <.001) ; the intensive care unit length of stay was 1.1 and 1.8 hours (P=.014), respectively. The incidence of acute myocardial ischemia was lower in the main group (2.8% vs 12.2%, P=.026).Conclusions: Goal-directed hemodynamic and fluid therapy significantly improves MVR outcomes and reduces the risk of postoperative complications and long-term use of cardiovascular drugs.